APLIKASI TEKNOLOGI BUDIDAYA TANAMAN PAKAN RAMAH LINGKUNGAN TERHADAP KUALITAS HIJAUAN (Studi Pemanfaatan Pupuk Organik Kascing dan Sistem Tanam) - Suarna, I Wayan (Bumi Lestari; Vol 4 No 2)
Chemical analysis of forages was conducted at Animal nutrition Laboratory, Faculty of Animal Husbandry Udayana University to study the effect of casting organic fertilizer on Quality in Grass-legume Association. Field experiment was consisted of two factors as follows: (1) three types of cropping systems (grass monoculture, legume monoculture, and grass-legume association), (2) four levels of casting organic fertilizer (0, 10, 20, and 30 t ha-1). The experiment design was a randomized block design arranged in factorial pattern and was replicated three times. The results showed chemical compossition of forage in association system at 20 t ha-1 casting had a higher quality and a higher Ca and P contents, a lower NDF and lignin contents, whereas : ADF, hemisellulose, and cellulose contents were not significantly different.
Keywords: Casting, Cropping System, and Forage Quality.